2018
DOI: 10.6061/clinics/2018/e489s
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and biology of cutaneous human papillomavirus

Abstract: Cutaneous human papillomaviruses (HPVs) include β- and γ-HPVs, in addition to a small fraction of α-HPVs. β-HPVs were first isolated from patients with the rare genetic disorder Epidermodysplasia verruciformis, and they are associated with the development of nonmelanoma skin cancer at sun-exposed skin sites in these individuals. Organ transplant recipients also have greater susceptibility to β-HPV infection of the skin and an increased risk of developing nonmelanoma skin cancer. In both immunosuppressed and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 106 publications
1
23
0
2
Order By: Relevance
“…After the initiation of the malignant process, E6 and E7 continue to play an essential role in the propagation of the carcinogenic process [54]. In contrast, beta HPV types are involved in the initiation of carcinogenesis but not in tumour persistence and tumour growth occurring in the absence of the viral genome [55]. E6 and E7 of both alpha and beta HPV types are involved in cell cycle alteration and inhibition of apoptosis [25].…”
Section: Mechanisms Of Beta Hpv Types Involved In the Development Of mentioning
confidence: 99%
See 1 more Smart Citation
“…After the initiation of the malignant process, E6 and E7 continue to play an essential role in the propagation of the carcinogenic process [54]. In contrast, beta HPV types are involved in the initiation of carcinogenesis but not in tumour persistence and tumour growth occurring in the absence of the viral genome [55]. E6 and E7 of both alpha and beta HPV types are involved in cell cycle alteration and inhibition of apoptosis [25].…”
Section: Mechanisms Of Beta Hpv Types Involved In the Development Of mentioning
confidence: 99%
“…Clinical and histopathological analysis showed that in the case of transplantation patients most of the cSCCs arise on common warts and are located especially on the sunexposed areas [55]. The immunosuppression and exposure to ultraviolet radiation are two factors with synergistic activity for the development of skin cancers [78].…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%
“…Human papillomaviruses are a large family of small double stranded DNA viruses that are divided into five genera (alpha-, beta-, gamma-, mu-and nu-papillomaviruses) [1]. Among these genera, members of the alpha-papillomavirus genus are most clearly connected to tumorigenesis [2,3]. Alpha-papillomaviruses are designated high-risk or low-risk based on their relative likelihood that their infections cause cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the great majority of α-PVs infect mucosa in the anogenital epithelia, some viral genotypes from this genus were originally described as cutaneous, together with β-and γ -PVs. However, regarding β-PVs, it has been difficult to determine their individual role in cutaneous malignancies due to their high diversity and their dissemination throughout many tissues such as the skin, the oral cavity, the nasal mucosa, and the anogenital region (Nunes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%